Mimetite and polymineralic mimetite-pyromorphite-vanadinite single crystals from the Sowie Mts, Poland - Szełęg Eligiusz; Janeczek Janusz; Juroszek Rafał; Danila Marta (Mineralogia)
Millimeter-sized crystals of mimetite and pyromorphite, and polymineralic mimetite-pyromorphite-vanadinite crystals occur in quartz-baryte vein within paragneisses of the Sowie Mts, SW Poland. Three morphologically different mimetite crystals and a polymineralic crystal were examined by electron probe micro-analysis (EPMA), back-scattered electrons (BSE) imaging, Raman microspectroscopy, and X-ray composition mapping. Mimetite occurs as well-developed crystals, crystals built up of sub-parallel individuals due to autoepitaxial growth, and crystals extensively etched. All of the mimetite crystals are zoned with respect to pyromorphite molecule content with sharp increase up to 23 mol% in the outermost zones. The apparent vanadinite crystal actually consists of oscillatory-zoned pyromorphite + minor vanadinite core, intermediate zones composed of pyromorphite, two mimetite zones intercalated by a band of oscillatory pyromorphite and minor vanadinite, and vanadinite mantle. EPMA data show a limited miscibility between all three minerals in the polymineralic crystal. Most analyzes cluster around 10 mol% of ternary solid solution with the maximum value of ca. 30 mol%. X-ray elemental maps reveal sharp boundaries between compositionally contrasting zones in the crystal core. In mimetite zones, the substitution of As by P does not exceed 0.43 atoms per formula unit (apfu). In the vanadinite mantle, As + P does not exceed 0.30 apfu. The distribution of Pb is uniform throughout the crystal with the highest Ca/Pb ratio of 0.03. The observed sequence of crystallization in the polymineralic crystal can be explained by the relative changes in ions concentrations at the crystal/solution interface, i.e. within the diffusion boundary layer, in accord with the models of the autocatalytic crystal growth. The authors hypothesize that kinetically driven fast growth of the polymineralic crystals resulted in precipitation of discrete mineral phases with very limited anionic substitutions.